“Of pearls and stars, he made the verse”: the literary career of the founders of Brazilian Neurology - Pedro, Matheus Kahakura Franco (Arquivos de Neuro-Psiquiatria, 2021)
In the beginning of modern Neurology, between the 19th and the 20th centuries, neurologists often assumed simultaneous positions of intellectual prominence and gained significant cultural credentials. Not only observers and admirers of music, literature, and the fine arts, many neurologists and neuroscientists worldwide developed significant cultural careers. When studying the careers and lives of the founders of Brazilian Neurology, one finds only sparse information on their cultural activities, which are often relegated to side notes. Therefore, the author aims to focus on the literary output of some of the most important early Brazilian neurologists, who excelled in poetry or longer written forms and were eventually immortalized by the Academia Brasileira de Letras: Antônio Austregésilo, Aloysio de Castro, Deolindo Couto, and Miguel Couto, contextualizing their artistic production in their respective academic lives.
Keywords: Deolindo Couto; Aloysio de Castro; Antônio Austregésilo; History of Neurology; Neurology and Literature